Korelasi Pola Hidup Sehat pada Aktivitas Fisik dan Status Gizi terhadap Status Kebugaran Serta HRQL (Health – Reated Quality of Life) Peserta Didik - Nina Kristina; Cerika Rismayanthi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine: 1) the relationship between healthy lifestyle and fitness status of students of SMP Negeri 3 Gunung Bintang Awai, South Barito Regency; 2) the relationship between physical activity and fitness status of students, then the collected data were first validated using triangulation of sources and methods, then analyzed using interactive data analysis techniques which include data collection, reduction, presentation, and drawing conclusions; 3) The relationship between nutritional status of students and physical activity of students of SMP Negeri 3 Gunung Bintang Awai, South Barito Regency; 4) The relationship between HRQL of students and healthy lifestyle and fitness level at SMP Negeri 3 Gunung Bintang Awai, South Barito Regency. Purposive sampling was used to collect research data from a population of 56 students in class VIII A and B. Physical activity using PAQ-A, physical fitness using TKJI, HRQL (Health-Related Quality Of Life) using a questionnaire, and nutritional status using a weight scale, height using a stadiometer, and BMI calculation are closed questionnaire instruments and healthy lifestyle questionnaires. Data were analyzed using descriptive and inferential statistical analysis, including Pearson correlation tests and regression analysis. The results showed a significant positive correlation between healthy lifestyles, physical activity, and nutritional status with overall fitness and HRQL. Students who adopted a healthy lifestyle, had a high level of physical activity, and had good nutritional status tended to have better levels of physical fitness and a higher quality of life. The conclusion of this study is that these three factors mutually contribute to improving physical fitness and HRQL in students. The implication of this study is the importance of comprehensive interventions to improve healthy lifestyles, encourage physical activity, and ensure optimal nutritional status in students of SMP Negeri 3 Gunung Bintang Awai, South Barito Regency. Keywords: Physical Activity, Healthy Lifestyle, Nutritional Status, Fitness Status